Dapur Gambir Di Kebun Lama Cina, Jejak Kegiatan Perekonomian Masa Lalu Sebagai Potensi Sumber Daya Arkeologi Pulau Lingga - Lucas Partanda Koestoro (Berkala Arkeologi Sangkhakala, 2011)
AbstractOn the Lingga Island, in a location known as Kebun Lama Cina, it was found the remains of ‘Dapur Gambir’( a place for processing gambier) in the village area Kelume. It was also found ceramics fragment, the pedestals, ‘talud’ stone, and the tread and the remaining that’s colouring the site. Tracking the place with the rest of the culture that is often reported, throught the qualitative descriptive approach it has been identified the traces of past economic activity of Lingga Island, it happened when the area was an important part of the kingdom of Riau Lingga in the 18 century until yhe end of the early 10 century. As one of the objects of archeological resource potential. Its exixtance must be addressed wisely, concerning the preservation and the improvement of community welfare.